PAKAIAN PENGHULU PESISIR SELATAN DALAM KARYA SENI LUKIS - Drs. Efrizal, M.Pd., BUSTARIZAL, Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2018)
The purpose of this final work is to visualize the form, function and meaning of the  lothes of Penghulu Pesisir Selatan. It purpose to make people know well about the  ature of Minangkabau through that project. The form of this art is showing the  haracteristic which represent theme as a concept and the characters are related  ach other. Then, this creation is using the contemporary realist technique. In this  echnique the author begins the proces with preparation, elaboration, synthesis and  ealization the concept, then it will be appeared through exhibition to the public. The creations are given sensitiveness to the people who care with the nature of  inangkabaua artwork that contains with beauty, philosophy and history.Keywords: The clothes of Penghulu Pesisir Selatan, art painting